PENERAPAN LDKS UNTUK MENINGKATKAN MOTIVASI BELAJAR DAN HASIL BELAJAR SISWA SEKOLAH DASAR - Hilyatus Shofi (Lembaga Pendidikan dan Pelatihan Sindotech, 2023)
This study aims to improve learning motivation and learning outcomes of elementary school students through LDKS (Student Leadership Basic Exercises). This research is a form of action with two cycles consisting of three meetings each. The subjects of this study were teachers and 25 grade IV students of SD Islam Al-Inayah. At the stage of learning implementation, teachers have implemented LDKS appropriately and maximally so that learning motivation and student learning outcomes increase. The average student learning motivation in cycle I was 56.3% while in cycle II it was 85.1%, so it can be concluded that there was an increase in student learning motivation by 28.8%. The average percentage of completeness of learning outcomes in cycle I was 45.9% while in cycle II it was 81.9% so it can be concluded that there was an increase in the completeness of student learning outcomes by 36%. From the results of the comparison between cycle I and cycle II, the average class was obtained at 67.21 and 78.45. The conclusion of this study is that the application of LDKS can improve learning motivation and learning outcomes of elementary school students.